Single-Dose 13-Valent Conjugate Pneumococcal Vaccine in People Living With HIV – Immunological Response and Protection - Romaru, Juliette; Bahuaud, Mathilde; Lejeune, Gauthier; Hentzien, Maxime; Berger, Jean-Luc; Robbins, Ailsa; Lebrun, Delphine; N’Guyen, Yohan; Bani-Sadr, Firouzé; Batteux, Frédéric; Servettaz, Amélie (Frontiers in Immunology, 2021)
Background Patients living with HIV (PLHIV) are prone to invasive pneumococcal disease. The 13-valent conjugated pneumococcal vaccine (PCV13) is currently recommended for all PLHIV, followed in most guidelines by a 23-valent polysaccharide pneumococcal vaccine. Data are scarce concerning the immunological efficacy of PCV13 among PLHIV. Objective To assess the immunological response at one month, and the immunological protection at 1-, 6-, and 12 months in PLHIV with a CD4 cell count above 200 cells/µl after a single dose of PCV13, as measured by both ELISA and opsonophagocytic assay (OPA). Methods PLHIV with CD4 cell count >200 cells/µl were included. Specific IgG serum concentrations for eight serotypes by ELISA and seven serotypes by OPA were measured at baseline, 1-, 6-, and 12 months after the PCV13 vaccination. Global response was defined as a two-fold increase from baseline of specific IgG antibody levels (μg/ml) assayed by ELISA or as a four-fold increase in OPA titer from baseline, for at least five serotypes targeted by PCV13. Global protection was defined as an IgG-concentration ≥1 µg/ml by ELISA or as an opsonization titer ≥LLOQ by OPA for at least five tested serotypes targeted by PCV13. Factors associated with global response and global protection were assessed using logistic regression. Results Of the 38 PLHIV included, 57.9% and 63.2% were global responders, 92.1% and 78.9% were globally protected at one month, and 64.7% and 55.9% were still protected at 12 months, by ELISA and OPA respectively. A CD4/CD8 ratio of >0.8 was significantly associated with a better global response by OPA (OR=6.11, p=0.02), and a CD4 nadir <200 was significantly associated with a poorer global response by ELISA (OR=0.22, p=0.04). A CD4 cell count nadir <200 and age over 50 years were associated with poorer global protection by OPA at M1 (OR=0.18, p=0.04) and M12 (OR= 0.15, p=0.02), respectively. Plasma HIV RNA viral load <40 copies/ml was significantly associated with a better global protection at M1 by ELISA and OPA (OR=21.33, p=0.025 and OR=8.40, p=0.04) Conclusion Vaccination with PCV13 in these patients induced immunological response and protection at one month. At one year, more than half of patients were still immunologically protected.